Storage Limitation Statements: Temperature--Fungicides - Frederick M. Fishel (EDIS)
This guide provides general temperature effects on storage properties of agricultural fungicides. A table is included which lists many of the common agricultural fungicides registered for use in Florida with storage statement limitations listed.  This document is PI-122, one of a series of the Agronomy Department, UF/IFAS Extension. Original publication date May 2006.